2011
DOI: 10.2220/biomedres.32.29
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of the collagen and elastin sponge derived from salmon as an artificial dermis and scaffold for tissue engineerin

Abstract: Collagen sponge is one of the medical materials that are frequently used in clinical medicine. However, the problem of prion disease harmfully affected the usage of mammals-derived medical materials. Since there have been no reports about prion disease occurring in marine products, we produced the collagen and elastin sponge (CES) made from salmon, and investigated whether the CES could be a substitute for mammalian collagen sponge. Fibroblasts were seeded in the CES to examine whether the CES could be used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 41 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…The other dressing material used was CS (TERUDERMIS; Olympus Terumo Biomaterials Corp., Tokyo, Japan), comprising collagen derived from the dermis of young cows (Figure 1A). 13 It consisted of lower and upper layers; the lower layer was CS, while the upper layer was a silicon membrane. In the present study, we only used the lower layer to compare collagen with HxAlGltn.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other dressing material used was CS (TERUDERMIS; Olympus Terumo Biomaterials Corp., Tokyo, Japan), comprising collagen derived from the dermis of young cows (Figure 1A). 13 It consisted of lower and upper layers; the lower layer was CS, while the upper layer was a silicon membrane. In the present study, we only used the lower layer to compare collagen with HxAlGltn.…”
Section: Resultsmentioning
confidence: 99%
“…In order to prevent postoperative scar contracture, a number of absorbable materials are used in surgeries to cover the epithelial defects of wounds 11,12 . Wound dressings made of atelocollagen sponges are often used in oral and maxillofacial surgeries 13,14 . Atelocollagen not only functions as a scaffold for the surrounding cells, but also promotes cell infiltration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The film implanted in a full-thickness wound in the rat dorsal region resulted in regeneration of tissue with similar morphological appearance to that of native rat dermis tissue and significantly enhanced the formation of blood capillaries [67]. Two years later, a study reported a collagen sponge developed from salmon [68] for tissue engineering applications as an artificial dermis scaffold. To analyze the function of the sponge scaffold in tissue engineering, proliferation of fibroblast was investigated, and positive results were obtained.…”
Section: Collagenmentioning
confidence: 99%
“…These polymers have the proper flexibility and are thus more appropriate. Additionally, natural polymers can be modified and their properties can be regulated in vitro (2735).…”
Section: Introductionmentioning
confidence: 99%